PRESCHOOL EDUCATION AS A DETERMINANT OF EDUCATIONAL ATTAINMENT: AN ANALYSIS OF SERBIA - Vuksanović, Nemanja; Joksimović, Ljubinka (Economic Annals, 2017)
The subject of this paper is preschool education as a determinant of students’ educational attainment in Serbia and factors that influence whether a Serbian child is included in preschool programmes. This paper aims 1) to assess how attendance of preschool programmes in Serbia affects a student’s educational attainment in terms of mathematical, reading, and scientific literacy; 2) to explore how preschool education differs for students who occupy different positions in the distribution of educational attainment; and 3) to examine the determinants of a child in Serbia receiving preschool education. The analysis is based on data from PISA2012 testing. In order to assess the significance and nature of the effect of preschool education on educational attainment in terms of mathematical, reading, and scientific literacy we use unconditional quantile regression. To analyse factors that affect whether a child is included in the preschool programme we apply probit regression. Unconditional quantile regression results suggest that the sign and intensity of the effect of preschool education for more than a year are positive and increasing. The results of the probit regression show that socio-economic family background and parental status in the labour market are the factors that determine whether the student will attend preschool education for more than a year. The results indicate that the educational system in Serbia reproduces poverty and social exclusion.